Vegan at home : recipes for a modern plant-based lifestyle - Solla Eiríksdóttir (Phaidon Press Ltd, 2022)
"145 simple and delicious vegan recipes from celebrated Icelandic cook and culinary celebrity/entrepreneur Solla Eiríksdóttir - perfect for home cooks starting out on their vegan journey or for those looking for new inspiration. For Solla Eiríksdóttir the key to successful vegan cooking is simple: easy-to-make recipes that are tasty and delicious. Here, she shows how to make great vegan food at home for all kinds of occasions, whether a quick work-day lunch or special dinners with friends. The perfect book for a modern, plant-based lifestyle, its three sections cover: Basics (vegan staples such as nut milks and tofu); Everyday (breakfast through to dinner); and Celebrations, which spotlights a meal strategy for larger events. The 75 basic recipes for vegan staples such as nut milks and tofu provide the foundation for the 70 dishes that will take you from breakfast through to dinner. Recipes for hearty Vegetable Tagine, nourishing Sweet Potato and Smokey Lentils, and super light Spicy Strawberry Pavlovas will surprise and delight in equal measure" -- Publisher's description.